2020
DOI: 10.1101/2020.08.11.245761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of stimulus intensity on neural envelope tracking

Abstract: Objectives: The last years there has been significant interest in attempting to recover the temporal envelope of a speech signal from the neural response to investigate neural speech processing. The research focus is now broadening from neural speech processing in normal-hearing listeners towards hearing-impaired listeners. When testing hearing-impaired listeners speech has to be amplified to resemble the effect of a hearing aid and compensate peripheral hearing loss. Until today, it is not known with certaint… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In several studies, it has been shown that increasing task demand due to lower stimulus intensity or increasing background noise is associated with an increase in the latency of neural responses in continuous speech (Mirkovic et al, 2019;Verschueren et al, 2020) or in CAEP-responses (Billings et al, 2015;Van Dun et al, 2016;Maamor and Billings, 2017;McClannahan et al, 2019). Similarly, for NH listeners, we found that as speech understanding decreases, the delay of neural responses increases.…”
Section: Higher Neural Tracking Of Speech In Hearing-impaired Listenerssupporting
confidence: 73%
See 3 more Smart Citations
“…In several studies, it has been shown that increasing task demand due to lower stimulus intensity or increasing background noise is associated with an increase in the latency of neural responses in continuous speech (Mirkovic et al, 2019;Verschueren et al, 2020) or in CAEP-responses (Billings et al, 2015;Van Dun et al, 2016;Maamor and Billings, 2017;McClannahan et al, 2019). Similarly, for NH listeners, we found that as speech understanding decreases, the delay of neural responses increases.…”
Section: Higher Neural Tracking Of Speech In Hearing-impaired Listenerssupporting
confidence: 73%
“…McClannahan et al (2019) remarked that differences in the audibility of the stimulus might explain the differences in neural response latency. Indeed, Verschueren et al (2020) observed that reduced audibility increases the latency of the neural responses to continuous speech. However, at a comfortable loudness (at intensities of 60 dB or higher in a NH population), the latency reaches a plateau.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations